TRAFFIC FLOW MODEL WITH INFLUENCE OF PASSENGER TRANSPORT - Popov , Stanislav (World Science, 2024)
This work deals with accomplishing the first objective of the research. It is determined that passenger route traffic can be divided into traffic by city roads and traffic by country roads. Outside cities vehicles use mostly public roads with two or four lanes. Country roads with four lanes are characterized by the following features: there are no obstacles like crossroads with pedestrian crossings at the same level; traffic ban is applied to certain road users; top speeds can be formed; there are accidents with route vehicles involved. There is substantial analysis of the statistical data concerning accidents with route vehicles involved on public roads, and the accidents mentioned are characterized by significant severity. The number of people who are injured or die in the result of one road accident with a passenger route vehicle involved is significantly bigger as compared to other kinds of road accidents. The accidents under discussion are characterized by extreme severity in conditions of high speeds on public roads as compared to road sections of other types. All this demonstrates the relevance of the direction that has been chosen for scientific research. Passenger route traffic safety is indirectly taken into account only when the route is planned and the indicator is added to the route passport. The information that the route passport provides refers to existing rail crossings and traffic accident areas. These specified elements are entered into the route scheme and are cited as a list. At present there are no tools to calculate the degree of danger; also there are no methods to organize a route that takes into account passenger route traffic safety on route sections as part of the relevant traffic flows. With the existing accidents statistics and corresponding severity indicators taken into account, the scientifically practical objective to develop a method to estimate passenger route traffic safety on public roads is clear. In accordance with the task proposed, the object, the subject, the goal and objectives of the research have been formulated in the article. For every level of the traffic flow analysis, a theoretical basis for forming traffic safety of passenger route vehicles within their interaction with other vehicles in the traffic flow has been formulated. It has been proposed to reveal negative phenomena which precede road accidents and occur in the traffic flow due to passenger route vehicles traveling at a set speed and at set intervals. These phenomena should be represented as deviations in kinematic characteristics of the traffic vehicles flow from similar characteristics of the passenger route vehicles flow.